Personal Branding: An Innovative Approach to Life Design Education - Lora Louise Broady (CERN IdeaSquare Journal of Experimental Innovation)
This case study introduces personal branding as an innovation in Career and Life Design. While Life Design offers a roadmap for navigating complex career paths, it requires a deep understanding of one’s identity, values, and aspirations. Personal branding can be a valuable complement to Life Design, providing individuals with a structured process for self-discovery and expression. By integrating principles of identity theory, self-concept theory, and brand management into a curriculum focused on personal brand development, students are empowered to construct meaningful and fulfilling life paths. The findings described in this case study suggest that personal branding can serve as a powerful tool for self-discovery, career exploration, and overall life design. Future research should explore the long-term impacts of personal branding education on career outcomes and overall life satisfaction.